Design front rake angle of PDC bit based on SolidWorks simulation method - Xiaoming HAN; Chenxu LUO; Xingyu HAN (Institute of Advanced Engineering and Science, 2016)
In order to solve the bit front rake angle parameter selection problem of under different coal rock, it is proposed in polycrystalline diamond compact no core bit as the research object, and established a bit compact two-dimensional stress model of cutting teeth. The result shows that the front rake angle is the factor of cutting force and the drilling efficiency. Application of SolidWorks simulation carries out the finite element simulation analysis respectively to different front rake angle of bit model under the condition of soft rock and hard rock. Form the simulation it concludes that under the condition of soft rock and hard rock, the optimal front rake angle is 10° and 15° respectively. It is obtained that the strength of the bit is largest and the life is longest on the best front rake angle of bit.